New records of the family Agathotanaidae (Crustacea: Tanaidacea) in the Antarctic, with remarks on Arthrura monacantha (Vanhöffen, 1914) - Jóźwiak, Piotr; Błażewicz-Paszkowycz, Magdalena (Zootaxa, 2011)
Based on the material collected during the ANDEEP III, BIOPEARL and USAP Expeditions, two new species of the family Agathotanaidae (Paranathrura arctowskii n. sp. and Paragathotanais ipy n. sp.) are described, together with new records of Paranarthrura fortispina Sieg, 1986. Additionally the first record of a male of Arthrura monacantha (Vanhöffen, 1914) is presented. The possibility of the development of eggs and mancas outside the marsupium is considered.